Approaches to Reducing Normal Tissue Radiation from Radiolabeled Antibodies - Hiroyuki Suzuki; Kento Kannaka; Tomoya Uehara (MDPI AG, 2024)
Radiolabeled antibodies are powerful tools for both imaging and therapy in the field of nuclear medicine. Radiolabeling methods that do not release radionuclides from parent antibodies are essential for radiolabeling antibodies, and practical radiolabeling protocols that provide high in vivo stability have been established for many radionuclides, with a few exceptions. However, several limitations remain, including undesirable side effects on the biodistribution profiles of antibodies. This review summarizes the numerous efforts made to tackle this problem and the recent advances, mainly in preclinical studies. These include pretargeting approaches, engineered antibody fragments and constructs, the secondary injection of clearing agents, and the insertion of metabolizable linkages. Finally, we discuss the potential of these approaches and their prospects for further clinical application.